Oxidation of copper nanowire based transparent electrodes in ambient conditions and their stabilization by encapsulation: application to transparent film heaters. (17th January 2018) - Celle, Caroline; Cabos, Anthony; Fontecave, Thomas; Laguitton, Bruno; Benayad, Anass; Guettaz, Laure; Pélissier, Nathalie; Nguyen, Viet Huong; Bellet, Daniel; Muñoz-Rojas, David; Simonato, Jean-Pierre
Abstract: Whereas the integration of silver nanowires in functional devices has reached a fair level of maturity, the integration of copper nanowires still remains difficult, mainly due to the intrinsic instability of copper nanowires in ambient conditions. In this paper, copper nanowire based transparent electrodes with good performances (33 Ω sq −1 associated with 88% transparency) were obtained, and their degradation in different conditions was monitored, in particular by electrical measurements, transmission electron microscopy, x-ray photoelectron spectrometry and Auger electron spectroscopy. Several routes to stabilize the random networks of copper nanowires were evaluated. Encapsulation through laminated barrier film with optical clear adhesive and atmospheric pressure spatial atomic layer deposition were found to be efficient and were used for the fabrication of transparent film heaters.